2017
DOI: 10.1155/2017/1215254
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dyonic Thin-Shell Wormholes in Low-Energy String Theory

Abstract: Considerable attention has been devoted to the wormhole physics in the past 30 years by exploring the possibilities of finding traversable wormholes without the need for exotic matter. In particular, the thin-shell wormhole formalism has been widely investigated by exploiting the cut-and-paste technique to merge two space-time regions and to research the stability of these wormholes developed by Visser. This method helps us to minimize the amount of the exotic matter. In this paper, we construct a four-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[131] by adding a constant part to the classical action and choosing that constant part in a way normalizing the absorption probability to unity. [ 111,132 ] In our derivation, the same result is obtained by normalizing the emission probability to the absorption probability, namely normalΓμ=Pem,μPab,μ=expbadbreak−4πωAfalse(rHfalse)Bfalse(rHfalse),$$\begin{eqnarray} \Gamma _\mu = \frac{P_{em,\mu }}{P_{ab, \mu }} = \exp {\left\lbrace -\frac{ 4\pi \omega }{\sqrt {A^\prime (r_H) B^\prime (r_H)}}\right\rbrace}, \end{eqnarray}$$and from this rate formula, one reads the Hawking temperature, which is inversely linked with the Boltzmann factor β$\beta$, TH=β1$T_{H}=\beta ^{-1}$ as TH=A(rH)B(rH)4π,$$\begin{align} T_H = \frac{\sqrt {A^\prime (r_H) B^\prime (r_H)}}{4 \pi }, \end{align}$$which differs from the Hawking temperature of Schwarzschild black hole by the presence of the conformal factor φfalse(rfalse)$\varphi (r)$ in the metric (). In fact, it takes the explicit form (TH)γ>0=M2πrH21e…”
Section: Tunneling Of Symmerons and Other Particles: Hawking Temperaturementioning
confidence: 99%
“…[131] by adding a constant part to the classical action and choosing that constant part in a way normalizing the absorption probability to unity. [ 111,132 ] In our derivation, the same result is obtained by normalizing the emission probability to the absorption probability, namely normalΓμ=Pem,μPab,μ=expbadbreak−4πωAfalse(rHfalse)Bfalse(rHfalse),$$\begin{eqnarray} \Gamma _\mu = \frac{P_{em,\mu }}{P_{ab, \mu }} = \exp {\left\lbrace -\frac{ 4\pi \omega }{\sqrt {A^\prime (r_H) B^\prime (r_H)}}\right\rbrace}, \end{eqnarray}$$and from this rate formula, one reads the Hawking temperature, which is inversely linked with the Boltzmann factor β$\beta$, TH=β1$T_{H}=\beta ^{-1}$ as TH=A(rH)B(rH)4π,$$\begin{align} T_H = \frac{\sqrt {A^\prime (r_H) B^\prime (r_H)}}{4 \pi }, \end{align}$$which differs from the Hawking temperature of Schwarzschild black hole by the presence of the conformal factor φfalse(rfalse)$\varphi (r)$ in the metric (). In fact, it takes the explicit form (TH)γ>0=M2πrH21e…”
Section: Tunneling Of Symmerons and Other Particles: Hawking Temperaturementioning
confidence: 99%
“…In terms of energy density and pressure, thin-shell mass and its radial derivatives are given as The second derivative of the potential function at x = x 0 may be used to illustrate thin-shell stability as follows: [15] (i) For stable ⇒ V″(x 0 ) > 0,…”
Section: Stability Analysis Through Radial Linear Perturbationmentioning
confidence: 99%
“…Eiroa and Aguirre [14] investigated the stability of thin-shell spherical Lorentzian WHs in f (R) theory in the background of electromagnetic field by using symmetry preserving perturbation. In the framework of Einstein-Maxwell-dilaton theory, Övgün and Jusufi [15] formed a charged spherically symmetric dyonic thin-shell WH and demonstrated that the stable domain of the dyonic thin-shell WH can be increased in terms of electric charge, dilaton charge as well as magnetic charge. Mazharimousavi [16] demonstrated that thin-shell WH cannot be formed in the black hole spacetime solution of charged f (R) theory.…”
Section: Introductionmentioning
confidence: 99%
“…Varela [ 11 ] found stable thin‐shell WH solutions by assuming barotropic and non‐barotropic fluids. Jusufi and Ovgun [ 12 ] studied the stability of canonical acoustic thin‐shell WHs and Ovgun and Salako [ 14 ] investigated an acoustic thin‐shell WH within the context of neo‐Newtonian theory and found that changing the parameters of neo‐Newtonian theory led to stable states of the developed solution. Ovgun and Jusufi uncovered several intriguing findings while researching the stable configuration of dyonic thin‐shell WHs within the context of low‐energy string theory.…”
Section: Introductionmentioning
confidence: 99%